Early bi-canalicular silicone stent intubation in failed DCR with endoscopic visualization: a combined approach - Sreenivas, V.; Chaitanya, P.; Reddy, Manjoo (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic dacryosystitis is a common condition affecting the eye and presenting to ENT surgeons and ophthalmologists, and treated with DCR (dacryocystorhinostomy). In few cases there can be recurrence of symptoms following DCR surgery which can be treated with bi-canalicular silicone intubation. The aim of this study is to assess the effectiveness of an early bi-canalicular silicone intubation in patients with failed DCR using endoscopic visualisation. Methods: This was a prospective observational study. Thirteen cases of DCR operated for chronic dacryocystitis at St John’s Medical College Hospital were reviewed between January 2014 and February 2017. Endoscopic DCR was done for five patients and external DCR for eight patients, number of males were 5 (38%) and females were 8 (62%). Age: 9–73 years (avg: 40.5 years). Results: Nine patients had complete resolution of symptoms following the primary DCR (4 following external DCR and 5 following endonasal endoscopic DCR). Four patients had failed DCR with persistence of watering three months following primary DCR surgery. Re-DCR with bi - canalicular silicon stent intubation was done in failed cases. Postoperative follow up of all the four patients showed complete resolution of symptoms. Conclusions: Failed DCR surgeries can be effectively intubated using bi–canlicular silicon tubes in the early postoperative period following DCR surgery. Silicone tube intubation is the most safe and cost effective method. Endoscopic visualization gives an added advantage of localizing the cause for a failed DCR.